Penggunaan Media Tangga Pintar Satuan Berat untuk Meningkatkan Pemahaman Siswa pada Pelajaran Matematika Kelas III pada SD Negeri Malaka - Yufrizal Yufrizal (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This research discusses the smart ladder media for weight units to improve students' understanding of Class III Mathematics at SD Negeri Malaka. The research was motivated by problems found in the field regarding the low understanding of students in mastering the concept of measuring the weight of Class III students at SD Negeri Malaka. The aim of this research is to improve the abilities of Class III students at SD Negeri Malaka. in understanding the concept of measuring the weight of objects in Mathematics subjects. The target of this research was 20 Class III students at SD Negeri Malaka. This research uses a type of classroom action research. From the results of the analysis, it was found that students' understanding of weight measurements in Mathematics lessons showed that there had been an increase in the average from cycle I to cycle II, namely cycle I (68), cycle II (80). The conclusion of this research is that the use of smart ladder media for weight units can facilitate and provide students' understanding of weight units in Mathematics learning.